DATES AS A SUBSTITUTE FOR ADDED SUGAR IN TRADITIONAL FOODS - A CASE STUDY WITH IDLI - Manickavasagan, A.; Mathew, T. A.; Al-Attabi, Z. H.; Al-Zakwani, I. M. (Emirates Journal of Food and Agriculture, 2013)
Scientific evidences suggest that increased intake of added sugar is one of the major causes for dental caries, glucose intolerance, diabetes mellitus, cardiovascular diseases, obesity, hypertension and behavioural complications such as hyperactivity in children. In many parts of the world, consumption of added sugar is much higher than the dietary recommendation from health organizations. Several researchers have used dried fruits to sweeten the traditional foods as the functionality of the sugar incorporated within the structure of intact fruits is different than added sugar in human health. Date fruits have also been used in several forms such as syrups, spread, sugar and flour as a sweetener in food. The objective of this study was to develop acceptable idli (traditional Indian breakfast) with chopped dates, date paste and date syrup, and determine their sensory and chemical properties. Total phenol and vitamin C contents of dates idli were significantly higher than control idli with added sugar. The sensory properties of four idli products (idli with date paste, idli with date syrup, idli with chopped dates and control idli served with white sugar) were evaluated by 40 untrained panelists. The sweetness and aroma of the idli with chopped dates got significantly higher scores than other three idli products with no difference among them. Similarly the overall acceptability score of the idli with chopped dates was higher than other idli products. Panelists from a regular eaters group gave higher scores for the overall acceptability of developed idli products than first time consumers. In all sensory attributes and consumer types, idli with dates scored higher preference or at least equal preference with control idli and white sugar combination. There are ample opportunities to educate people and create awareness about preparation and consumption of traditional foods with dates in order to reduce added sugar intake.